Educación financiera en servidores públicos del Ministerio de Defensa Nacional de la ciudad de Loja. - Gonzalez Conde, Claudia Ines (2022)
Financial knowledge is a fundamental pillar to improve management skills and strengthen financial independence; the objective of this study is to develop a financial education program aimed at Public Servants of the Ministry of National Defense of the city of Loja. The present study has a quantitative - descriptive and cross-sectional approach because it was carried out in a specific period; the survey was used as an instrument to collect information, which was applied to 269 people who are part of the designed sample, therefore the main findings of the research are: in the first place, the military personnel prior to the financial training program present a "Regular" level of knowledge of financial education, since it is evident that there is no resolution of simple cases of simple interest and the lack of knowledge in concepts such as active and passive interest rate, or amortization tables; Secondly, after the socialization of the training program, the military public servants improved their qualitative qualification to an "Excellent" level, meaning that they went from a quantitative level of 40.57% to 98.33%, the percentage variation between the initial level of financial knowledge and post-training is 57.76% being a positive percentage variation; finally it is concluded, in the importance of strengthening the training programs in financial education in order to reach more population, regardless of their age and achieve that they make informed decisions that improve their family finances.